1998
DOI: 10.1039/a805360j
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clenbuterol on adrenal function in rats†

Abstract: The use of anabolic agents is illegal in the European Community but the effect of these agents on animal welfare is not well documented. The aim of this study was to evaluate whether the administration of anabolic agents, such as clenbuterol, causes stressful effects in rats, as reflected by the adrenal function. Anabolic doses of clenbuterol (1 mg kg-1, 99% purity) were administered orally by stomach tube daily for 45 d to female Long Evans rats (250-300 g, n = 50). Twenty-five animals were used as controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Although corticosterone, rather than cortisol, is the predominant adrenal corticosteroid in rats, technical difficulties prevented us from obtaining sufficient corticosterone measurements for statistical analysis. We observed roughly parallel changes in these two hormones, however, consistent with their overlapping biosynthetic pathways (Fauci et al, 1998) and with other studies showing parallel changes in release of corticosterone and cortisol (Illera et al, 1998;Szucs et al, 2001). Melatonin levels were unaffected relative to saline-injected controls at all sample times (Fig.…”
Section: Dmh Lesions Eliminate Circadian Rhythm Of Adrenal Corticostesupporting
confidence: 92%
“…Although corticosterone, rather than cortisol, is the predominant adrenal corticosteroid in rats, technical difficulties prevented us from obtaining sufficient corticosterone measurements for statistical analysis. We observed roughly parallel changes in these two hormones, however, consistent with their overlapping biosynthetic pathways (Fauci et al, 1998) and with other studies showing parallel changes in release of corticosterone and cortisol (Illera et al, 1998;Szucs et al, 2001). Melatonin levels were unaffected relative to saline-injected controls at all sample times (Fig.…”
Section: Dmh Lesions Eliminate Circadian Rhythm Of Adrenal Corticostesupporting
confidence: 92%
“…Chronic administration of ␤-agonists such as clenbuterol or salbutamol in rats almost invariably produces significant cardiac hypertrophy (78,123,386). Clenbuterol treatment in rats has also been shown to increase cortisol and corticosterone secretions and increase the size of the adrenal glands due to hyperplasia of adrenocortical cells (198).…”
Section: A Effects Of ␤-Agonists On Cardiac Muscle Structure and Funmentioning
confidence: 98%
“…Since CLE specifically binds to the β 2 -adrenergic receptor, a G proteincoupled receptor and then activates the heterotrimeric G protein -adenylate cyclase -cAMP productive pathway, CLE would induce directly apoptotic cell death in thymocytes, which would cause the reduction of thymus mass, although there was no significant difference between both groups in the present study. Furthermore, Illera et al (26) showed that anabolic dosage of CLE caused adrenal gland hypertrophy and increased secretions of glucocorticoids such as corticosterone and cortisol in rats. Thus, CLE administration-induced reduction of thymus mass would be partially caused by glucocorticoid-induced apoptotic cell death in thymocytes.…”
Section: Cle Administration-induced Changes Of Visceral Organ Weightsmentioning
confidence: 99%